Neoadjuvant immunotherapy and neoadjuvant chemotherapy in resectable non-small cell lung cancer: A systematic review and single-arm meta-analysis - Wang, He; Liu, Tingting; Chen, Jun; Dang, Jun (Frontiers in Oncology, 2022)
Background: It remains uncertain whether neoadjuvant immune checkpoint inhibitor (nICI) is superior to neoadjuvant chemotherapy (nCT) in resectable non-small cell lung cancer. In addition, there are outstanding questions for nICI such as the ideal treatment mode and predictors. Methods: PubMed, Embase, Cochrane Library, Web of Science, and scientific meetings were searched for eligible single-arm or multi-arm trials until December 31, 2021. The primary outcomes of interest were major pathological response (MPR), pathological complete response (pCR). The random-effect model was used for statistical analysis. Results: Twenty-four trials of nICI (n = 1043) and twenty-nine trials of nCT (n = 2337) were identified. nICI combination therapy was associated with higher MPR (63.2%, 95% CI: 54.2%-72.1%) and pCR (35.3%, 95% CI: 27.4%-43.3%) rates compared to nCT (16.2%, 95% CI: 7.5%-25.0%, P < 0.001 and 5.5%, 95% CI: 3.5%-7.5%, P < 0.001) and nICI monotherapy (23.3%, 95% CI: 12.7%-33.8%, P < 0.001 and 6.5%, 95% CI: 1.7%-11.2%, P < 0.001). As for safety, nICI monotherapy had the best tolerability; nICI combination showed similar surgical resection rate and higher R0 resection rate compared to nCT. PD-1 inhibitor and high PD-L1 expression (≥1% or ≥50%) were correlated with higher MPR and pCR rates compared to PD-1 inhibitor and PD-L1 expression <1%. Conclusions: nICI combination therapy is associated with higher MPR and pCR rates compared to nCT and nICI monotherapy. PD-1 inhibitor seems to be superior to PD-L1 inhibitor. PD-L1 status appears to be predictive of MPR and pCR for patients receiving nICI.